Modification of a Soft Drink by Adding Calcium Carbonate Nanoparticles to Prevent Tooth Erosion - Esmaeili Khoozani N; Bahrololoom ME; Bagheri R (Shiraz University of Medical Sciences, 2014)
Statement of Problem: One of the factors in dental erosion is consumption of acidic soft drinks. Although the effects of various additives to acidic soft drinks for the prevention of tooth erosion have been assessed, little data have been published on the possibility of preventing the erosion through soft drinks containing calciumcarbonate nanoparticles. Objectives: To examine the erosive factors of 7up soft drink and to determine the possibilities of decreasing or preventing the erosion phenomenon of the soft drink containing calcium-carbonate nanoparticles. Materials and Methods: 7up soft drink was assigned as control and a set of solutions containing 0.04, 0.05, and 0.06 vol % of the nano-particles were assigned as the experimental solutions. The pH, titratable acidity (TA), calcium and phosphorus concentrations and degree of saturation with respect to enamel hydroxyapatite (DSEn) were calculated. These parameters refer to assessment of erosive potential of the soft drinks. The erosion potential was evaluated based on the micro-hardness and the structural changes of the tooth surface using scanning electron microscopy (SEM). Data were analyzed using Kruskal-Wallis H test,andBonferroni-adjusted Mann- Whitney U test. Results: An increase in the nano-additive content of the solutions increased pH and DSEn; however, it decreased the TA (P < 0.05). There was a significant difference between the micro hardness in the control and experimental groups (p<0.001). SEM imagesrevealed less surface erosion of the specimens stored in the higher nanoadditive concentrations. The modified drink containing 0.06% nano-additive revealed the highest hardness with no evidenceof tooth erosion. Conclusions: Adding calcium carbonate nanoparticles to soft drinks can be considered as a novel method to reduce or prevent tooth erosion